How Burnout Affects Turnover Intention? The Conditional Effects of Subjective Vitality and Supervisor Support - ERDİLEK KARABAY, MELİSA (ARDABIL INDUSTRIAL MANAGEMENT INST, 2018)
Although numerous researchers in the literature have tried to show that low levels of supervisory support contributing to job burnout and turnover, the moderating effects of supervisor support and subjective vitality on this interaction still keep unclarified. This paper examines the effect of burnout on turnover intention of 295 employees, who are employed in Turkish health sector. It is also aimed whether supervisor support and subjective vitality have moderating effects on job burnout-turnover intention relationship. The findings show that the two dimensions of burnout namely emotional exhaustion and depersonalization positively affects turnover intention. Moreover, the moderating effects of supervisor support and subjective vitality on the relationship between burnout (emotional exhaustion and depersonalization) and turnover intention are statistically significant. Specifically, the levels of subjective vitality and supervisor support increases, the burnout-turnover intention relationship gradually strengthens. Managerial applications and further research directions are provided. (C) AIMI Journals
Keywords: Burnout; Turnover Intention; Subjective Vitality; Supervisor Support; Emotional Exhaustion; Depersonalization; PERCEIVED ORGANIZATIONAL SUPPORT; JOB BURNOUT; ROLE STRESS; OCCUPATIONAL STRESS; SELF-REGULATION; SOCIAL-WORKERS; HEALTH; PERFORMANCE; ASSOCIATIONS; SATISFACTION